Proximate composition of three species of Scomberoides fish from Sri Lankan waters - Sutharshiny, S.; Sivashanthini, K. (Asian Network for Scientific Information, 2011)
Evaluating the proximate composition of food fish is the most important aspect in fish nutrition. The present study was carried out to determine the flesh quality of Scomberoides lysan, S, tol and S, commersonianus fish species which correspond to different grade of inclination of the Sri Lankan consumers. Major nutrient compositions of raw muscle like protein, lipid, moisture, carbohydrate and ash were estimated. Proximate compositions were varied among the species. The highest moisture content was present in S. lysan (75.67%) and the lowest in S. commersonianus (72.57%). The ash content estimated in S. lysan, S. tol and S. commersonianus were 1.42, 1.49 and 1.6%, respectively. Carbohydrate was present in very low level (<0.3%) in all fish species. Protein content was estimated as 19.47±0.16%, 18.99±0.51% and 21.68±0.65% in S. lysan, S. tol and S. commersonianus respectively. Lipid content for S. lysan, S. tol and S. commersonianus was recorded as 0.89±0.005%, 0.594±0.113% and 1.00±0.12%, respectively. The results revealed that the highest protein content, lipid and ash content were recorded in S. commersonianus (21.68, 1.00 and 1.6%, respectively) whereas the lowest lipid content was reported in S. tol (0.59%). Marked significant differences (p<0.05) were observed among Scomberoides fish species for the mean moisture, protein, lipid, carbohydrate and ash contents. From the results S. commersonianus can be suggested as an ideal dietetic food among the three fish analyzed.
Keywords: Ash; Carbohydrate; Lipid; Moisture; Protein; S. Commersonianus; S. Tol; Scomberoides lysan